Chronic Actinic Dermatitis With Eosinophilia And Elevated Total Immunoglobulin E Serum: A Case Report (International Journal of Environmental Sciences, 2025)
Chronic actinic dermatitis (CAD) is a chronic photosensitivity disease, characterized by pruritic eczematous lesions, mainly in sun-exposed areas. The etiology of CAD is still not well understood. Furthermore, increased levels of eosinophils and total immunoglobulin E (IgE) are common in CAD patients due to shifment of T-helper 2 (Th2) immunity from the T-helper 1 (Th1)/Th2 balanced status. We present a case of CAD in a 72-year-old male with a 7-month history of pruritus and erythematous lesions on his neck, forearms, and both thighs. The patient underwent skin biopsy, revealing histopathological features of spongiotic reaction in the epidermis and exocytosis of inflammatory lymphocytes which consistent with CAD. Laboratory results showed an elevated IgE serum and peripheral blood eosinophils. The patients were managed with photoprotection, topical corticosteroids, and oral antihistamine. Careful history taking, dermatological examination, and appropriate laboratory investigations are essential for diagnosis of CAD. In addition to blood eosinophilia and elevated IgE, there is evidence that UV radiation induces Th2 immunity through a variety of mechanisms. Interleukin-36γ (IL-36γ), IL-8, chemokine (C-C motif) ligand 17 (CCL17), and CCL18 have been shown to correlate with both eosinophil count and elevated IgE serum levels. Subsequent investigations should be conducted to determine the exact mechanism by which Th2 immunity and other factors such as IL-36 can contribute to the development of CAD.